Preparation of boron carbon oxynitride phosphor films with compositional and spectral tunability by chemical vapor deposition. Issue 20 (15th October 2022) - Katsui, Hirokazu; Harada, Katsuyoshi; Liu, Zheng; Kondo, Naoki; Hotta, Mikinori
Abstract: Boron carbon oxynitride (BCNO) phosphor films exhibiting tunable chemical compositions and photoluminescence (PL) spectra were grown by chemical vapor deposition utilizing a laser using an alkylamido precursor with an oxidation gas. BCNO films exhibiting a dense, uniform microstructure and a turbostratic boron nitride (BN) structure was grown on a silicon substrate at 1323 K. Chemical bonding states investigated by X-ray photoelectron spectroscopy and X-ray absorption near edge structure of the BCNO films were like the hexagonal BN powder counterparts. The typical chemical compositions of BCNO phosphor films were B0.46−0.47 C0.12−0.14 N0.30−0.34 O0.07−0.11, which was varied by regulating flow rates of the oxidation gas. The PL spectra generated under excitation at 360 nm exhibited multiple emission bands at 386, 405, 430, 473, 534, and 570 nm. BCNO films grown using higher C and O concentrations exhibited intensified PL peaks at 534 and 570 nm.